Supply Response of Paddy in East Java: Policy Implications to Increase Rice Production - Imade Yoga Prasada; Aura Dhamira; Agus Dwi Nugroho (Universitas Muhammadiyah Yogyakarta, 2018)
An increasing population in recent decades has led to the need for increasing the availability of food, so it is necessary to increase the production of paddy as quickly as possible. The aim of this research was to know the supply response of paddy in East Java to various price factors and non-price factors. In this research, the supply response was estimated by the paddy harvest areas in East Java using Cobb-Douglas model and Nerlove partial adjustment, and econometric analysis including stationarity test, cointegration test, and Error Correction Model (ECM). The data used in this research consisted of paddy harvest areas, grain price, corn price, irrigated land area and rainfall amount from 1991 to 2015. The speed of short-term adjustment to the long-term supply of rice was 2.79% and was corrected in the next period. In the short run, all variables did not have a high responsiveness to paddy supply, but in the long run, the irrigation area was very responsive to paddy supply in East Java with a value of elasticity of 1.79. Supply of paddy can be increased by increasing the real price of unhulled rice, the irrigated land, and harvested area of the previous period.